PERJANJIAN BUILD AND TRANSFER ANTARA PEMERINTAH DAERAH DENGAN PIHAK SWASTA DALAM PENYEDIAAN INFRASTRUKTUR (Studi Di Nusa Tenggara Barat) - Asikin, Zainal (Jurnal Dinamika Hukum, 2012)
Undergoing local authority does not always bring with it advantage to the local government, but this may challenge the local government to make efforts to support and fund its governmental develop-ment. On of the ways out is by working in cooperation with private enterprises based the law of local execution. This study is intended to analize the cooperative agreement of local government with build and transfer model which is adopted widely by some local governments in Indonesia. Through  normative juridical study along with statute and case approaches, it is found the coopera-tive agreement of build and transfer in Indonesia is ruled by some official regulations which have different substantive points and have conflicted norms and vague rules related to legal subyect, procedures or mechanism of having agreement. In the future  it  is needed to issue legal decision re-lated to cooperative agreement between the local government and private enterprises which is more comprehensively in order to resolve the legal affairs or disputes.  Key words:  build and transfer, infrastructure, bouwheer